Intraoperative Transesophageal Echocardiography in Nepal - Maskey, Arun; Sharma, Deewakar; KC, Man Bahadur; Rajbhandari, Sujeeb; Sharma, Jyotindra; Koirala, Ramesh; Pradhan, Sidhartha; Koirala, Bhagwan (Nepalese Heart Journal, 2003)
Intraoperative transesophageal echocardiography is an important tool for intraoperative evaluation of mitral valve repair. A total of 29 patients who underwent intraoperative transesophageal (TEE) between 25th June, 2001 to 30th Dec, 2002.at Shahid Gangalal National Heart Centre, Kathmandu were studied. The age ranged from 14 to 48 years with mean age of 30 years. There were 11 male and 18 female patients. Twenty three patiants had mitral valve repair for Severe mitral regurgitation, which was successful in 15 patients and rest underwent prosthetic valve replacement. Five patients had undergone closed mitral commissurotomy with 4 patients having successful dilatation and 1 patient had annular tear which was converted to open repair with mitral valve ring. One patient had huge aortic aneurysm which was successfully repaired. TEE has been proven to be extremely useful in intraoperative evaluation of mitral valve repair and may help to a timely raintervention, if needed. This is the first study of intraoperative transesophageal achocardiography in Nepal.